Eco-education: A response to the Anthropocene and an uncertain future - Sandra Abegglen; David Blundell; Jessie A. Bustillos Morales (Educational Futures, 2021)
This paper explores the potential of eco-pedagogies for fostering new environmental and consumption imaginaries. It departs from the Anthropocene to posthumanism, using Karen Barad’s posthumanist quantum entanglements as a way to understand how our lives are enmeshed with commercial and carbon consumption cultures. Two case studies are presented aiming to illustrate how reductive current approaches to environmental education are exemplifying the importance of our sense of place and the potentialities of ‘no toys’. The paper argues that what we need is a fundamental shift towards eco-education that surpasses sustainability as a curricular topic but offers a more radical and practical way of living. We need to foster human to non-human connections that allow for new materialities and forms of living that reach beyond schools and schooling – ‘a more-than human’ approach.